PERANAN RELAWAN BACA DALAM MENINGKATKAN LITERASI MASYARAKAT DESA LEMBANG LOHE KECAMATAN KAJANG KABUPATEN BULUKUMBA - Az-Zahra, Fathimah; Arsyad, Susalti Nur (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2020)
This study aims to obtain information and knowledge based on data or facts that are valid, correct and reliable about the role of reading volunteers in improving community literacy. This research was conducted from June 2020 to August 2020 in Lembang Lohe Village, Kajang District, Bulukumba Regency. This research is a qualitative research. With data collection techniques used are observation, interviews, documentation, and literature. Researchers get research data from informants. The key informants of this research are the coordinator and facilitator who is also the manager of the Smart House. Meanwhile, the core informants were reading volunteers and community learning participants in Lembang Lohe Village, Kajang District, Bulukumba Regency. Based on the results of these field findings, reading volunteers have a series of programs to support their role in increasing the literacy of rural communities. The programs implemented in each activity have gradually increased interest in reading, writing and arithmetic. Starting from a sense of interest in books, a sense of pleasure in reading, a sense of need for reading, and an attitude of trying to find a reading. The programs that support the improvement of literacy in rural communities are studying every weekend, and a mobile library. Despite the many obstacles faced on their journey to improve the literacy of rural communities, reading volunteers are still active in carrying out their programs.